THE ANALYSIS OF THE REVENUES AND EXPENSES DURING COVID-19 PANDEMIC: THE CASE OF COMPANIES OF THE SECTOR I-ACCOMMODATION AND FOOD SERVICES OF THE BELGRADE STOCK EXCHANGE - Milašinović, Marko (The Business of Tourism, 2022)
The operations of companies in the field of tourism and catering have changed to a significant extent with the emergence of the COVID-19 pandemic. The aim of the work is to determine whether there have been changes in the income and expenses of hospitality companies in the Republic of Serbia with the onset of the COVID-19 pandemic. The research in the paper was carried out on the example of 15 companies listed on the Belgrade Stock Exchange within Sector I-Accommodation and Food Services, where their income statements for 2019 and 2020 were used as a data source. For research purposes, horizontal analysis and ratio analysis were used. In the largest number of observed hospitality companies in 2020, a decrease in income and expenses was recorded compared to 2019. Also, it was determined that in the largest number of observed companies, there was an increase in the ratio of total expenses and total income during the observed period. The results of the work can be of importance primarily to the management and owners of catering companies, in order to see the impact of the COVID-19 pandemic on financial performance, but they can also be useful to investors when making decisions about investing their funds, i.e. to economic policy makers when defining measures to overcome the consequences of the crisis.